Increase in Viral Load in Patients With SARS-CoV-2 Delta Variant Infection in the Republic of Korea - Kim, Jeong-Min; Rhee, Jee Eun; Yoo, Myeongsu; Kim, Heui Man; Lee, Nam-Joo; Woo, Sang Hee; Jo, Hye-Jun; Kwon, Donghyok; Lee, Sangwon; Yoo, Cheon Kwon; Kim, Eun-Jin (Frontiers in Microbiology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spread rapidly, causing in COVID-19 being declared a global pandemic by the World Health Organization. The key variants include alpha, beta, gamma, and delta; these exhibit high viral transmission, pathogenicity, and immune evasion mechanisms. The delta variant, first confirmed in India, was detected in the majority of COVID-19 patients at the recent wave in the Republic of Korea. Here, the features of the delta variant were compared to the earlier waves, with focus on increased transmissibility. The viral load, from the initial days of infection to 14 days later, was compared based on epidemiological data collected at the time of confirmed diagnosis. The increased viral load observed in the delta variant-led infections influences the scale of the wave, owing to the increased rate of transmission. Infections caused by the delta variant increases the risk of hospitalization within 14 days after symptom onset, and the high viral load correlates with COVID-19 associated morbidity and mortality. Therefore, the future studies should compare the trend of disease severity caused by the high viral load of delta variant with previous waves and analyze the vaccine effects in light of the delta variant of fourth wave.